Influence of Printing Orientation on the Mechanical Properties of Provisional Polymeric Materials Produced by 3D Printing - Kaiahara, Fábio Hideo; Pizi, Eliane Cristina Gava; Straioto, Fabiana Gouveia; Galvani, Lucas David [UNESP]; Kuga, Milton Carlos [UNESP]; Arrué, Thalita Ayres; Junior, Ageu Raupp; Só, Marcus Vinícius Reis; Pereira, Jefferson Ricardo; Vidotti, Hugo (MDPI, 2025)
This study investigates the impact of printing layer orientation on the mechanical properties of 3D-printed temporary prosthetic materials. Traditionally, temporary prostheses are fabricated using acrylic resin (polymethyl methacrylate), but advancements have introduced bis-acrylic resins, CAD/CAM-based acrylic resin (milled), and 3D printing technologies. In 3D printing, material is manufactured in overlapping layers, which can be oriented in different directions, directly affecting the material’s resistance. Specimens were designed as bars (2 mm × 2 mm × 25 mm) and grouped according to their printing orientation: BP0 (0 degrees), BP45 (45 degrees), and BP90 (90 degrees). The models were created using Fusion 360 software (version 2.0.12600) and printed on a 3D DLP printer with DLP Slicer software (Chitu DLP Slicer, CBD Tech, version v1.9.0). The bars were then subjected to 3-point bending tests using an Instron Universal Testing Machine to measure Flexural Strength (FS) and Flexural Modulus (FM). Results demonstrated that the BP90 group exhibited the highest Flexural Strength (114.71 ± 7.61 MPa), followed by BP45 (90.10 ± 8.45 MPa) and BP0 (80.90 ± 4.01 MPa). Flexural Modulus was also highest in the BP90 group (3.74 ± 3.64 GPa), followed by BP45 (2.85 ± 2.70 GPa) and BP0 (2.52 ± 2.44 GPa). Significant statistical differences (p < 0.05) were observed, indicating changes in the mechanical properties of the 3D-printed material. The study concludes that printing orientation significantly influences the mechanical properties of temporary prosthetic materials, making the selection of an optimal orientation essential to enhance material performance for its intended application.
Keywords: computer-aided design; denture; partial; printing; resin cements; temporary; three-dimensional